A multigroup analysis of the effect of cognitive appraisal on nurses' psychological distress - Simães, C. (2019)
Background: Cognitive appraisal constitutes an important mechanism in the process of human adaptation to work environment and occupational stress. In this domain, nursing professionals are one of the occupational groups most affected by job stress, suffering high levels of psychological distress. Objectives: The aim of this study was to analyze the moderator effect of shift work and the type of job contract on the relationship between work cognitive appraisal and nurses’ psychological distress, and to explore the interaction effect of the two moderator variables on that relationship. Methods: A sample comprised of 2,310 Portuguese registered nurses completed a sociodemographic and professional questionnaire: the Primary and Secondary Cognitive Appraisal Scale, and the General Health Questionnaire-12. Data were analyzed through structural equation modeling and multigroup analyses considering the following groups: (a) “shift” versus “nonshift work”; (b) “precarious job contract” versus “nonprecarious job contract”; and (c) “shift and precarious” versus “shift and nonprecarious” versus “nonshift and precarious” versus “nonshift and nonprecarious.” Results: Data confirmed the invariance for the measurement model, but the structural model presented a significantly worse adjustment for all grouping variables, showing the moderator effect of shift work and job contract and of their interaction. Differences tests in structural path coefficients revealed that shift work moderated the relationship between challenge perception and psychological distress—which was stronger for shift work nurses—and that a higher threat perception was related to greater psychological distress, especially in nurses with a precarious job contract. Among the four categories of interaction between job contract and shift work, cognitive appraisal became central in predicting nurses’ mental health, explaining more variance in the group that did shift work and had a nonprecarious job contract. Discussion: The study results highlight the need to develop occupational health intervention programs to promote nurses’ mental health, focusing on reducing work perception as a threat and on making nurses’ jobs more challenging and controllable.